Perceptions and beliefs in sarcoidosis - Ireland, J.; Wilsher, M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
Background: Sarcoidosis is a chronic multisystem disease with a high prevalence of depression although this is often not recognised. It is not known how patients perceive their disease or the medications required for treatment.We hypothesised that perceptions of illness and beliefs about medications may relate to psychological distress in this condition.Methods: 81(42 female) patients with sarcoidosis completed the following: Hospital Anxiety and Depression Scale, Illness Perception Questionnaire, Beliefs about Medications Questionnaire. Demographic and clinical data were collected and the physician’s perception of symptom severity and relationship to sarcoidosis recorded. Results: The prevalence of depression (23%) and anxiety (33%) was high and related to self reported symptoms of sarcoidosis.Those on current treatment reported different illness perceptions than those not, and illness perceptions related to anxiety and depression scores.The majority of the sample felt that sarcoid medications were unnecessary but few patients reported concerns about potential adverse consequences of taking them. Beliefs about medications were related to illness perceptions but not associated with anxiety or depression scores or with clinical perception of disease state. There were significant gender differences in perceptions of illness and beliefs about medications. Conclusions: These data confirm earlier reports that anxiety and depression are common in patients with sarcoidosis and in turn perceptions of illness impact on emotional wellness in this disorder. Use of the Illness Perceptions Questionnaire in clinical practice may help to identify those patients who would benefit from interventions to change their perceptions of illness.